Diminished water yield coefficient of glacial catchments in Northwest China - Jing Liu; Aihua Long; Mingjiang Deng; Qiang An; Xiaoya Deng; Zhenliang Yin; Pei Zhang; Xiaoying Lai; Xinchen Gu (Journal of Hydrology: Regional Studies)
Study region: 19 glacial catchments located in Northwest China. Study focus: The water yield coefficient (denoted as WYc) of glacier catchments in Northwest China has changed over the past six decades, closely linked to shifts in land cover dynamics. However, quantifying the impacts of climate and land cover changes on glacier catchments remains challenging due to the complexity of glacier hydrological processes and the scarcity of long-term glacier runoff data. In this study, the Budyko equation was coupled with a glacier runoff model to enable quantitative analysis of the factors driving changes in water yield (WY). Path analysis was then employed to assess the direct and indirect effects of climate and landscape changes on the WYc. New hydrological insight for the region: The results indicated that 14 out of 19 catchments experienced a decline in WYc, particularly in those with greater glacier coverage. Glacier retreat and increased vegetation greenness adversely affected WYc by increasing the catchment parameter, with effects of −26.42 % and −25.21 %, respectively. Although overall WY in the catchments has increased—driven primarily by increased precipitation and glacier storage loss, with contribution rates of 100.66 % and 25.05 %, respectively—the diminished WYc is expected to decelerate the rate of WY increase. This trend poses significant challenges for water resource management in arid and water-scarce regions.